Reinforcement of acrylonitrile butadiene rubber with waste rubber ash using ionizing radiation. Issue 2 (8th June 2015) - El‐Nemr, K.F.; Hassan, M.M.; Saad, E.A.; Hamdy, E.M.
Abstract : Composites of acrylonitrile butadiene rubber with waste rubber ash (WRA) were prepared in the laboratory by a two‐roll mill. Gamma radiation at different doses (0 to 150 kGy) was applied to curing of acrylonitrile butadiene rubber composites loaded with reinforcement filler (ash powder, 5–40 parts by weight per hundred parts of rubber [phr]). WRA was characterized by Fourier‐transform infrared spectroscopy and X‐ray diffraction. Mechanical and thermal properties of prepared composites were investigated. The results show that the concentration of WRA up to 40 phr and irradiation dose up to 100 kGy improve the mechanical properties of composites. On the other hand, the thermal stability of the composites improved by adding 40 phr of WRA. J. VINYL ADDIT. TECHNOL., 23:117–124, 2017. © 2015 Society of Plastics Engineers